Dissolution of a Representative Body of a Municipality as a Kind of ‘Innocent’ Responsibility of Deputies: A View from Russia - SOLOVEV, Sergey Gennadievich; TITOVA, Elena Viktorovna (Journal of Advanced Research in Law and Economics, 2019)
The article analyzes such a special measure of the legal responsibility of deputies of the municipal level of the Russian government as the dissolution of the representative body of a municipality. The peculiarity of the legal responsibility of deputies of a local representative body is the fact that responsibility occurs without establishing their fault. The key theoretical and practical problems associated with the substantive and procedural aspects of the existing mechanism of ‘objective imputation’ with regard to municipal deputies due to the failure of the local representative body to take measures to execute the court decision, as well as not holding an authorized meeting, are considered. A set of legal measures aimed at improving the content of the analyzed legal structure is proposed.